Is group diabetes education effective on hemoglobin A1c level? - Cansu, Güven Barış; Taşkıran, Bengür; Yorulmaz, Göknur; Doğan, Hülya; Dinçtürk, Cevahir (The European Research Journal, 2018)
Objectives. Diabetes education decreases hemoglobin A1c (HbA1c) level by 1% in patients with diabetes mellitus. In addition, education delays development or progression of complications by improving psychosocial, clinical, and behavioural aspects of diabetes mellitus, improves quality of life, modifies life style behaviours including healthy eating and regular exercise. In this study, we aimed to evaluate efficacy of diabetes group education programme called diabetes school on glycemic control by comparing HbA1c levels of patients with diabetes mellitus measured before and after education. Methods. Electronic medical records of patients with DM who were registered to diabetes school executed by endocrine units of two hospitals between 2015 and 2017 were retrospectively evaluated. Diabetes school programme was composed of 90 minutes sessions a week for 4 consecutive weeks. Education sessions were executed in a didactic and interactive pattern. Results. The attendees (n = 65) had signicantly lower HbA1c levels after the education programme (before 9.09 ± 2.46%, after 7.88 ± 1.90%; p = 0.001) than the non-attendees (n = 41) (before 8.96 ± 2.35%, after 8.35 ± 2.00%; p = 0.091). Insulin users had significantly higher baseline HbA1c values and benefited more than non-insulin users (p < 0.0001). Conclusions: The diabetes school education programme has positive impact on glycemic control in patients with diabetes mellitus. A large team may lessen the burden of education sessions on health specialists. The school executed by a team consisting of specialists may reach a larger number of patients while the patients get the opportunity to repeat the sessions anytime they need.